Mouthwashes: a review on its efficacy in preventing dental caries - Eko Fibryanto; Lidia Santoso (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Biofilm plays an important role in the etiology of caries, and can be removed through chemical approach using mouthwash, which has some advantages over the mechanical one. Nowadays, there are a lot of mouthwashes with many active ingredients that have been developed. Aim: To review some mouthwashes’ efficacy in preventing dental caries.Discussion: As recent studies showed that Streptococcus mutans can’t be the sole predictor of caries risk, it is suggested that the mouthwashes are also tested on the other cariogenic bacteria, to better estimate its role in reducing caries risk. It has also been proven that as an adjunctive method, mouthwashes has the ability to decrease oral microbial load and cariogenic plaque, even though the most effective way in controlling caries is still mechanical tooth brushing with fluoride toothpastes. However, long-term clinical studies are still needed to confirm the efficacy of some mouthwashes in caries prevention.Conclusion: Mechanical tooth cleaning using fluoride toothpastes remains the main and most effective way in controlling caries. The use of mouthwash, despite its potential in reducing caries risk, is limited to some people with certain conditions as an alternative method, or as an adjunction to the mechanical tooth cleaning for increasing its efficacy.